Direct detection and identification of viruses in saliva using a SpecID ionization modified mass spectrometer - Pierre Alusta; Angel Paredes; Marli Azevedo; Lisa Mullis; Dan Buzatu (PLoS ONE, 2025)
The COVID-19 (SARS-CoV-2) pandemic has led to a significant mortality globally and persistent health challenges in many survivors. Early accurate diagnosis, surveillance, identification of cohorts, and prophylaxis are considered essential measures to reduce the spread of infectious viral pathogens such as SARS-CoV-2. A reliable, fast, high-throughput screening method that can detect viral particles and identify the pathogenic virus in infected individuals could help to reduce the spread of the next viral threat through quick knowledge and implementation of appropriate prevention strategies. Since respiratory viruses are typically present in nasal and oral secretions, saliva is a good target for testing for viral infections. Saliva testing has slowly gained popularity in the diagnostics based on biomarkers and other constituents ranging from organic compounds ( e . g ., food additives), peptides, and even microorganisms. Polymerase chain reaction (PCR) remains the gold standard for sensitive detection of SARS-CoV-2 infection in biological samples. However, while PCR testing for COVID is sensitive and widely used by hospitals, the method has a false-negative rate of 15–20% and is kit-based necessitating the development of alternative methods of detection that provide higher accuracy. This paper describes the use of a SpecID Mass Spectrometer that can detect the presence of viral particles in saliva at very low levels (<500 virions/0.5 ml). The main goal of this study was to demonstrate that our previously developed, portable, mass spectrometry based method, SpecID, could also be sued for detecting viruses in saliva, including but not limited to SARS-CoV-2; the SpecID method has the potential to provide a reliable solution that overcomes some of the challenges with molecular testing like PCR.